PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBANTU MUSIK INTERAKTIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV UPT SPF SD INPRES BONTOMANAI - Umar, Nuraisyah; Takdirmin; Ilhamsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem in this study is low learning outcomes. This study aims to determine the effect of the Talking Stick learning model, supported by interactive music, on mathematics learning outcomes. This study was a pre-experimental study. The research design used a one-group pretest-posttest design. The population was all fourth-grade students at the UPT SPF SD Inpres Bontomanai, consisting of two classes: Class IV A and Class IV B. The sampling technique used was random sampling. Random sampling is a random sampling technique. The sample in this study was students of Class IV A. The research instruments used were pretest and posttest test sheets. Data analysis techniques used were descriptive statistical data analysis and inferential data analysis. Based on the data obtained, the average learning outcome before the treatment (pretest) was 54.30, while the learning outcome after the treatment (posttest) was 83.73. These results indicate that the Talking Stick learning model, supported by interactive music, has an impact on students' mathematics learning outcomes. The results of the paired sample t-test show that the significant value (2-Tailed) is 0.000, which is smaller than the significance of 0.05. Thus, the decision taken is that (H_0) is rejected and (H_1) is accepted, indicating that there is a significant difference in learning outcomes before and after treatment. Based on the results of this study, it can be concluded that the application of the interactive music-assisted talking stick learning model has an effect on improving students' mathematics learning outcomes.